Legal therapeutic forms for litigation between doctors and patients - Mario Jorge Warde; Maria do Patrocinio Tenorio NUNES; Flavio Luiz Yarshell (Revista Brasileira de Cirurgia Plástica)
Highly empowered by knowledge and available information, patients are no longer a passive part of the patient-physician relationship but become more challenging and argumentative about their diagnoses and prescribed therapies. Part of the issues, especially regarding medical complications, may weaken this relationship, a phenomenon that has been described to enhance judiciary litigation against physicians worldwide. With this trajectory, there was a distance in this medical relationship. In this perspective, a wedge has been placed within the patient-physician relationship, delineating on one side a general public more suspicious of the services provided, and on the other side, a more worn-out doctor, with a defensive stance, hyper-specialized and consequently more technical and formalistic than humane and empathic. The reinforcement of medical information and communication between the parts strongly signal what is considered legal prophylaxis in medical services. Even so, complications do occur, and different attitudes do exist in the face of what may have happened. When this happens, one can count on a large legal system called “multi-doors,” able to accommodate the necessary contingency, depending on the diagnosis in the relations between the parts, for a legal therapy appropriate to each particular situation. Such “legal therapy” can occur by self-composition, as are the established methods of Mediation and Conciliation, no longer foreign to the health area, or by heterocompositive methods, among which are the already well-known methods of judicial adjudication and Arbitration.